2013
DOI: 10.1021/cn300206k
|View full text |Cite
|
Sign up to set email alerts
|

Two Cell Circuits of Oriented Adult Hippocampal Neurons on Self-Assembled Monolayers for Use in the Study of Neuronal Communication in a Defined System

Abstract: In this study, we demonstrate the directed formation of small circuits of electrically active, synaptically connected neurons derived from the hippocampus of adult rats through the use of engineered chemically modified culture surfaces that orient the polarity of the neuronal processes. Although synaptogenesis, synaptic communication, synaptic plasticity, and brain disease pathophysiology can be studied using brain slice or dissociated embryonic neuronal culture systems, the complex elements found in neuronal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 35 publications
(46 citation statements)
references
References 51 publications
1
45
0
Order By: Relevance
“…Previous data obtained from these cells using culture parameters established by the manufacturer indicates their functional characterization over two weeks in vitro, including evidence for their ability to generate three major voltage‐dependent currents (Na v , Ca v , and K v ) . However, analysis of neuronal performance over a two week period in a single culture environment is insufficient if these cells are to be considered for incorporation into chronic drug evaluation studies in vitro . Careful assessment of maturation end points and cell survival over an extended time‐course is necessary to justify incorporation of CDI's hiPSC‐derived neurons into body‐on‐a‐chip and other devices for chronic drug toxicity and efficacy studies.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous data obtained from these cells using culture parameters established by the manufacturer indicates their functional characterization over two weeks in vitro, including evidence for their ability to generate three major voltage‐dependent currents (Na v , Ca v , and K v ) . However, analysis of neuronal performance over a two week period in a single culture environment is insufficient if these cells are to be considered for incorporation into chronic drug evaluation studies in vitro . Careful assessment of maturation end points and cell survival over an extended time‐course is necessary to justify incorporation of CDI's hiPSC‐derived neurons into body‐on‐a‐chip and other devices for chronic drug toxicity and efficacy studies.…”
Section: Introductionmentioning
confidence: 99%
“…Previously, DETA has been used in conjunction with cytophobic surfaces to successfully culture as well as pattern cells into controlled configurations, providing the means to develop in vitro engineered cell networks for a variety of advanced culture applications . Furthermore, previous work has demonstrated that DETA is capable of promoting the survival and maturation of primary neurons in culture for extended periods . DETA, an analogue of spermine, has been shown to promote neuron survival in vitro through interactions with NMDA‐receptor complexes, and is also known to promote increased longevity in a number of model organisms by reducing the overproduction of harmful reactive oxygen species and autophagy regulation .…”
Section: Introductionmentioning
confidence: 99%
“…The anti-GluA2/3 antibody has been used in several recent immunocytochemical studies, which all have shown the expected characteristic staining pattern (Edwards et al, 2013;Sadeghi et al, 2014;Schuth et al, 2014;Peng et al, 2015).…”
Section: Experimental Procedures Antibodiesmentioning
confidence: 99%
“…Some of the more notable technological areas that have been employed include brain-device interfaces and surface technologies (Aregueta-Robles et al 2014 ;Helmke and Minerick 2006 ;El-Ali et al 2006 ;Cooke et al 2008 ;Edwards et al 2013 ); biomaterials such as synthetic extracellular matrices (Maclean et al 2016 ;Tibbitt and Anseth 2009 ;Theocharidis et al 2014 ); cell sources, particularly from stem cells (Merkle Florian and K. Eggan 2013 ); microfl uidic systems (Bhatia and Ingber 2014 ;Harink et al 2013 ;Barata et al 2015 ); and biomedical or biological microelectromechanical systems (Bio-MEMS). This chapter will focus on the in vitro modeling of the refl ex arc.…”
Section: Major Neural Systems That Have Been Engineered In Vitromentioning
confidence: 99%
“…The demonstrated success of both methods indicates the usefulness of silane surface chemistry for creating patterned neuronal circuits and other groups have adopted this methodology . Examples of the application of this silane-based surface technology in neural engineering include two-cell circuit patterns of hippocampal neurons (Edwards et al 2013 ;Molnar et al 2007a ) (Fig. 9.2 ) and feed-forward patterns for mimicking signal propagation in the nervous system (Natarajan et al 2013 ) (Fig.…”
Section: Direct Chemical Modifi Cation Of Surfacesmentioning
confidence: 99%